2015
DOI: 10.6018/analesdoc.18.2.222641
|View full text |Cite
|
Sign up to set email alerts
|

¿Qué papel juegan los bibliotecarios en las altmetrics?

Abstract: ¿QUÉ PAPEL JUEGAN LOS BIBLIOTECARIOS EN LAS ALTMETRICS?Nieves González-Fernández-Villavicencio * Biblioteca de la Universidad de SevillaMaría-Isabel Domínguez-Aroca * * Biblioteca de la Universidad de Alcalá (Madrid) Antonio Calderón-Rehecho * * * Biblioteca de la Universidad Complutense de MadridPablo García-Hernández * * * * Biblioteca de la Universidad de SalamancaResumen: Se busca identificar los pasos, a modo de hoja de ruta, que deben dar los bibliotecarios en la difusión, formación y asesoramiento de la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…In reality, academic libraries tend to provide research impact metric consultation services or documentation for researchers, who compile these metrics themselves (González-Fernández-Villavicencio et al, 2015;Lewis et al, 2015;Nordfeldt, 2015). In the United States, 79% of respondents to an Association of Research Libraries (ARL) survey who offer library-based, scholarly output assessment training say they include altmetrics in their sessions, and reportedly most respondents provide research impact assessment services to their patrons (Lewis et al, 2015).…”
Section: Altmetricsmentioning
confidence: 99%
“…In reality, academic libraries tend to provide research impact metric consultation services or documentation for researchers, who compile these metrics themselves (González-Fernández-Villavicencio et al, 2015;Lewis et al, 2015;Nordfeldt, 2015). In the United States, 79% of respondents to an Association of Research Libraries (ARL) survey who offer library-based, scholarly output assessment training say they include altmetrics in their sessions, and reportedly most respondents provide research impact assessment services to their patrons (Lewis et al, 2015).…”
Section: Altmetricsmentioning
confidence: 99%
“…Assim, informação e conhecimento são essencialmente, criações humanas, e nunca seremos capazes de administrá-los se não levarmos em consideração que as pessoas desempenham, nesse cenário, um papel fundamental. Além disso, como subsídio ao desenvolvimento da Sociedade da Informação as diretrizes emanadas da Association of College and Research Libraries (ACRL) (2000) constituem os parâmetros norteadores para suprir a necessidade da fluência e aprendizado quanto ao uso de fontes/recursos informacionais. Para a implementação dessas diretrizes, há a necessidade da criação de estratégias de ação facilitadoras e educativas que propiciem o desenvolvimento das competências e habilidades, que vão além do simples conhecimento de inovações tecnológicas, uma vez que depende fundamentalmente do discernimento e raciocínio dos seres humanos, o que envolve um tema de suma importância -Competência em Informação (BELLUZZO, 2007).…”
Section: Informação E Conhecimentounclassified
“…Also, from the 33 articles analyzed, 122 keywords from the authors were identified, the most frequent being Current Research Information Systems with six mentions, CRIS with four, and Animal welfare and behavior, CERIF, Metadata, Multistate research committee, Ontologies and Open Access with three. Most of the publications are aimed at reporting the uses of this type of systems and the information they manage, having applications in various areas, sectors, and levels, such as libraries, universities [25], [26] and globally [27]. A representative article of the mapping in this topic (APP), indicated that citation data from about 86,443 publications from 8359 researchers working in the social and natural sciences since 1970 were used, all stored in SICRIS, with the purpose of showing that citation distributions derived from individual publications have Zipfian properties [49].…”
Section: H Topics and Abstract (Rq7)mentioning
confidence: 99%
“…Another characteristic of CRIS is that they can be combined with institutional repositories [23] and perform an efficient exchange of information and reinforcement of their particular functions [24]. In addition, they have several applications, including their use in libraries and universities [25], [26], as well as in scientific communities [27]. The themes vary according to the research objectives of each institution publishing its results.…”
Section: Introductionmentioning
confidence: 99%